THE EFFECT OF MOTHER PERCEPTION AND FAMILY SUPPORT PROGRAM ON IMPROVING ANEMIA RELATED KNOWLEDGE AMONG PREGNANT WOMEN - Rukmaini Rukmaini (UPT Penerbitan Universitas Jember, 2017)
Background: Anemia during pregnancy was a health problem in the world including in Indonesia and it caused some negative impacts both for mothers and their babies. To reduce prevalence of anemia during pregnancy could be carried out by giving family support to improve the knowledge regarding anemia. Methods: A quasi-experimental study, two groups, pre – and post-test design was used in this study. The sample of this were pregnant women. The study was conducted on December 2016 to September 2017 at the Cikedal Public Health Center, Pandeglang District, Indonesia. Results: There was statistically significant improve in anemia knowledge among pregnant women in the experimental group (p<0.05). Conclusions: It is recommended that mother perception and family support program could be implemented in pregnant women to prevent anemia by improving applying this program. Keywords: Anemia, Pregnancy, Family support, Knowledge, Perception